Acute metabolic responses to a 24-h ultra-marathon race in male amateur runners - Waśkiewicz, Zbigniew (Springer-Verlag, 2011)
The study was conducted to evaluate the metabolic responses to a 24 h ultra-endurance race in male runners. Paired venous and capillary blood samples from 14 athletes (mean age 43.0 ± 10.8 years, body weight 64.3 ± 7.2 kg, VO(2max) 57.8 ± 6.1 ml kg(−1) min(−1)), taken 3 h before the run, after completing the marathon distance (42.195 km), after 12 h, and at the finish of the race, were analyzed for blood morphology, acid–base balance and electrolytes, lipid profile, interleukin-6 (IL-6), high-sensitivity C-reactive protein (hsCRP), and serum enzyme activities. Mean distance covered during the race was 168.5 ± 23.1 km (range 125.2–218.5 km). Prolonged ultra-endurance exercise triggered immune and inflammatory responses, as evidenced by a twofold increase in total leukocyte count with neutrophils and monocytes as main contributors, nearly 30-fold increase in serum IL-6 and over 20-fold rise in hsCRP. A progressive exponential increase in mean creatine kinase activity up to the level 70-fold higher than the respective pre-race value, a several fold rise in serum activities of aspartate aminotransferase and alanine aminotransferase, and a fairly stable serum γ-glutamyl transferase level, were indicative of muscle, but not of liver damage. With duration of exercise, there was a progressive development of hyperventilation-induced hypocapnic alkalosis, and a marked alteration in substrate utilization towards fat oxidation to maintain blood glucose homeostasis. The results of this study may imply that progressive decline in partial CO(2) pressure (hypocapnia) that develops during prolonged exercise may contribute to increased interleukin-6 production.